PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA PUSKESMAS DALAM KABUPATEN MUSI BANYUASIN - Tores, Ropal (Jurnal Ilmu Manajemen, 2015)
This research aims to determine the effect of service quality on patient satisfaction in outpatient health centers in the district Banyuasin, either jointly or partially. The study population was Outpatient At PHC In Musi Banyuasin which amounted to 92 people. The sampling technique that I useis the Random sampling, where some members of the population sampled. Data collection techniques used were questionnaires and documentation. The answers given by the respondents were analyzed quantitatively usingSPSS for Windows version 16. Data quality was tested with validity and reliability. In this research, testing the basic assumptions of multiple regression that includes test data normality, linearity test, multicollinearity and heteroscedasticity test. The results of this study indicate that jointly a significant difference betweenthe quality of service to the satisfaction Outpatient At PHC In Musi Banyuasin. While the partial results of this study showed no significant difference between the quality of service to the satisfaction Outpatient AtPHC In Musi Banyuasin. This study provides the latest evidence of the dimensions of service qualityon patient satisfaction and confirm the extent of the influence of the dimensions of service quality to the satisfaction of outpatients in health centers in the district Banyuasin. Evidence indicates that the variable reliability dominates in improving patient satisfaction in health centers in the district Banyuasin, which is where it is because over the influence of variable reliability compared with other variables.